APEGA 2025 Pensamiento Grafico entre Docencia, Representación e investigación (diségno, 2026)
From October 2nd to 4th 2025, the Escuela Técnica Superior de Arquitectura y Edificación (ETSAE) of the Universidad Politécnica de Cartagena (UPCT) hosted the Congreso Internacional de Expresión Gráfica Aplicada a la Edificación APEGA 2025 [1]. The biennial event has reached its XVII edition. The conference theme, Pensamiento Grafico/Graphic Thinking, refers to the process that evolves from conceptual synthesis to the representation of reality. [read more]